Hemoglobin mass and performance responses during 4 weeks of normobaric "live high-train low and high" - Kettunen, O.; Leppävuori, A.; Mikkonen, R.; Peltonen, J. E.; Nummela, A.; Wikström, B.; Linnamo, V. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Purpose To investigate whether 4 weeks of normobaric "live high-train low and high" (LHTLH) causes different hematological, cardiorespiratory, and sea-level performance changes compared to living and training in normoxia during a preparation season.